2001
DOI: 10.1021/bi002619j
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Control the Reactivity of the Interface Cysteine of Triosephosphate Isomerase from Trypanosoma brucei and Trypanosoma cruzi

Abstract: The amino acid sequences and X-ray structures of homodimeric triosephosphate isomerase from the pathogenic parasites Trypanosoma brucei (TbTIM) and Trypanosoma cruzi (TcTIM) are markedly similar. In the two TIMs, the side chain of the only interface cysteine (Cys14) of one subunit docks into loop 3 of the other subunit. This portion of the interface is also markedly similar in the two enzymes. Nonetheless, Cys14 of TcTIM is nearly 2 orders of magnitude more susceptible to the thiol reagent methylmethane thiosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
2
24
1
Order By: Relevance
“…In this work, we investigated which regions and which amino acids are responsible for these differences. This investigation was based on previous observations that have shown that in TIM only native dimers have catalytic activity and this is considered to be evidence that the quaternary structure of the enzyme is correct [8,9,23,24]. Even though there are also reports of activities in monomeric TIMs, these activities are very much lower than those reported for TbTIM and TcTIM [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we investigated which regions and which amino acids are responsible for these differences. This investigation was based on previous observations that have shown that in TIM only native dimers have catalytic activity and this is considered to be evidence that the quaternary structure of the enzyme is correct [8,9,23,24]. Even though there are also reports of activities in monomeric TIMs, these activities are very much lower than those reported for TbTIM and TcTIM [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Our steady-state kinetic characterization indicates that cTPI catalyzes the G3P to DHAP isomerization with a K m of 0.48 mM and a turnover number (k cat ) of 2565 s −1 , corresponding to a catalytic efficiency of 5.34 × 10 6 M −1 s −1 ; whereas pdTPI displayed a K m of 0.40 mM and a k cat of 2337 s −1 , corresponding to a catalytic efficiency of 5.48 × 10 6 M −1 s −1 . The observed K m values are comparable to constants from other plant TPIs, such as pea seed TPI, with a value of 0.44 mM (Turner et al, 1965), rye cTPI with a value of 0.6 mM, and its chloroplast counterpart with a value of 0.68 mM (Kurzok and Feierabend, 1984), spinach pdTPI (Tang et al, 1999) and TPIs from other organisms such as P. falciparum (Samanta et al, 2011) S. cerevisiae (Gonzalez-Mondragon et al, 2004), and T. cruzi (Reyes-Vivas et al, 2001; Table 1). In our hands pdTPI presents a k cat of 2337 s −1 that contrasts with the value of 424 s −1 previously reported (Chen and Thelen, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The triose phosphate isomerase (TIM) is also a central enzyme of the glycolytic pathway that has been studied in T. cruzi and in a number of pathogenic protozoa (Pérez-Montfort et al 1999, Reyes-Vivas et al 2001, Rodríguez-Romero et al 2002, Olivares-Illana et al 2006. Recently, two studies showed the possibility of developing new therapeutic agents against trypanosomes using TIM as a molecular target.…”
Section: The Energy Metabolismmentioning
confidence: 99%